2019
DOI: 10.1002/smll.201901201
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Coating of Patterned Carbon Nanotube Forest for Structured Lithium‐Ion Battery Electrodes

Abstract: Controlling the arrangement and interface of nanoparticles is essential to achieve good transfer of charge, heat, or mechanical load. This is particularly challenging in systems requiring hybrid nanoparticle mixtures such as combinations of organic and inorganic materials. This work presents a process to coat vertically aligned carbon nanotube (CNT) forests with metal oxide nanoparticles using microwave‐assisted hydrothermal synthesis. Hydrothermal processes normally damage delicate CNT forests, which is addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…These structures are interesting because they are mechanically robust, allow for a straight forward control of the microscale pore structure (honeycomb cell width), and straight electron transport though the aligned CNTs honeycomb walls which is advantageous in energy storage applications as shown for Li-ion batteries recently. [19] While several CNT honeycomb fabrication and modelling methods have been reported previously [7], [9], [12], [20]- [23], we found that the parameter space that results in defect free large area honeycomb structures is limited. To further understand the relevant factors affecting the honeycomb structure and defects we performed a design of experiment (DoE) analysis of the patterns and heights of CNT forests that result in high quality honeycomb electrodes.…”
Section: Introductionmentioning
confidence: 76%
“…These structures are interesting because they are mechanically robust, allow for a straight forward control of the microscale pore structure (honeycomb cell width), and straight electron transport though the aligned CNTs honeycomb walls which is advantageous in energy storage applications as shown for Li-ion batteries recently. [19] While several CNT honeycomb fabrication and modelling methods have been reported previously [7], [9], [12], [20]- [23], we found that the parameter space that results in defect free large area honeycomb structures is limited. To further understand the relevant factors affecting the honeycomb structure and defects we performed a design of experiment (DoE) analysis of the patterns and heights of CNT forests that result in high quality honeycomb electrodes.…”
Section: Introductionmentioning
confidence: 76%
“…The colloidal lithography-patterned VACNTs can also survive a microwave-assisted hydrothermal coating method (see Figure S7 ), for which we adapted a protocol reported by Li et al 52 and Jessl et al 53 to coat CNTs with Fe 2 O 3 nanosheets. While this method worked for short structures (as seen in the SEM images in Figure S7 a,b), it is more difficult for higher aspect ratio structures, as the narrow pores tend to close during drying due to capillary forces (as seen in the SEM images in Figure S7 c,d).…”
Section: Resultsmentioning
confidence: 99%
“…CNT, carbon nanotube; CVD, chemical vapor deposition; RIE, reactive ion etching; PS, polystyrene; Si, silicon to many researchers because of their high electroconductivity and lightweight advantages. 7,[34][35][36][37][38] As shown in Figure 5(C), hexagonally arranged microhole arrays were first prepared by photolithography that patterns positive tone PR resist by developing it with solvents. 34 Then, PVD was introduced to deposit catalyst, Fe/Al 2 O 3 , on the PR master mold.…”
Section: Top-down Lithography and Bottom-up Growthmentioning
confidence: 99%
“…For example, molecular assembly can be introduced to grow metal oxide nanopillar arrays with the assistance of a seed layer organized by sputtering 32 or spin-coating. 33 Advancing from that, carbon nanotube (CNT) micro 7,[34][35][36][37] /nanoforests 38 are rendered by bottomup assembly of C x H y molecules on a catalyst patterned by top-down lithography. Highly electroconductive and lightweight CNT micro/nanopillar arrays were obtained with high uniformity and periodicity.…”
Section: Introductionmentioning
confidence: 99%